Uji Validitas dan Reliabilitas Instrumen Pengukuran Kemampuan Literasi Siswa Sekolah Dasar - Hafidz Triantoro Aji Pratomo (Jurnal Terapi Wicara dan Bahasa, 2023)
Abstract Background: Literacy is a component of children's performance that is closely related to language skills. Metalinguistic awareness, reading comprehension, and dictation skills are some of the components of literacy that children need to master, especially in the early literacy learning process. The development of instruments is important to provide better clinical services, especially for children with learning disorders. Objectives: This article explains the value of validity and reliability of instruments testing metalinguistic awareness, reading comprehension, and dictation. Method: data collection using a direct test approach to children. The search for the validity and reliability of the instrument involved 45 children in grades 2-6 of elementary school. Test validity using correlation test. To find out the reliability value, use the Cronbach Alpha test. Results: The results of the correlation analysis found that all items on the metalinguistic awareness test, reading comprehension test, and dictation had good validity. All tests have reliability scores above 0.900. Conclusion: all instruments have fulfilled the initial rules in the development of an instrument or measuring instrument. Further development is needed, namely by collecting data with the target of determining norms according to the student's class. Keywords : validity, language, reliability, literacy, learning